Manajemen Peserta Didik dalam Meningkatkan Displin Siswa - Purba, Lailatul Adila (IKAMAS: Manajemen Pendidikan Islam, 2021)
This study was to determine the planning, implementation, evaluation, barriers, and solutions to face the obstacles of character education in improving students' disciplined attitudes. Data collection techniques used are observation, interviews, and documentation. Data were analyzed using data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data is by triangulation of sources and techniques. The results of this study indicate that the management of character education that is carried out is seen by the existence of measurable programs and activities in educational institutions referring to the interests of the quality of graduates through the implementation of good management. From the management of the school, it has an impact on character education in improving the disciplined attitude of students. However, the facts on the ground are still not optimal and the results are not as expected by all parties. This is due to the presence of several factors indicated as obstacles, both internal and external. So that educational institutions continue to improve themselves in organizing character education programs for students. The solution to improve the disciplined character of students is to build a synergy of all parties in the educational community to build a culture of discipline in school life. The recommendations given are related to the preparation of program plans and their implementation can be carried out involving all school stakeholders, so that all elements in school stakeholders know their roles, functions and responsibilities. Furthermore, each implementation of the school's extracurricular activities needs to be evaluated in order to measure the achievement of the goals that have been set and concrete improvement steps going forward.